La Medicina Fra Intelligenza Artificiale e Necessità di un Nuovo Umanesimo - Antonio Barracca; Stefano Ledda; Gianmaria Mancosu; Walter Melis; Maria Rosa Rinaldi; Patrizia Francesca Patricelli (AboutScience Srl, 2017)
Abstract non disponibile (Clinical_Management)